Magnaporthe oryzae : variabilidade genética e controle químico - Boaretto, Cristina (2016)
Among the factors responsible for the inefficiency of the wheat blast control strategies is the high variability of the fungus Magrnaporthe oryzae B. Couch (anamorph Pyricularia oryzae Cavara). To characterize the genetic variability of M. oryzae on wheat and weeds, it was conducted the identification the idiomorphs and sexuality of the pathogen in vitro with the help of testers, and in vivo variants, with the help of inoculations and genotyping. In the studied population the MAT1-1 idiomorph prevailed with the presence of complete sexual organs, and hermaphroditism among isolates of invasive plants. The occurrence of in vivo pathogen variants identified that the weeds are not just alternative hosts of the pathogen, but also the sources of variability. Regarding the chemical management for the control of wheat blast, it was evaluated in vitro the sensitivity of the mycelial growth and spore germination of M. oryzae isolates the antibiotic kasugamycin, to carbendazim fungicide, tricyclazole, tebuconazole, prothioconazole, mancozeb, azoxystrobin, trifloxystrobin, commercial mixture prothioconazole+trifloxystrobin, pyraclostrobin+ fluxapyroxad, the salicylhydroxamic acid (SHAM), the mixture SHAM+azoxystrobin. The fungicides were solubilized in PDA medium at concentrations of 0.00; 0.01; 0.10; 1.00; 10.00 and 100.00 mg L-1. The toxicity of the products was determined by means of EC50 (concentration necessary to inhibit 50% of the mycelium growth to 50% of the conidia germination) and sensitivity of the isolates classified into high, moderate, low and insensitive. For mycelium growth, isolates were mostly insensitive to the antibiotic kasugamycin, and highly sensitive to the other fungicides studied. For the germination of conidia, fungicides mancozeb and the mixture of pyraclostrobin + fluxopiroxade showed the highest fungitoxicity. Nineteen isolates showed insensitivity to azoxystrobin and SHAM showed fungitoxic potential for M. oryzae. The fungicidal deposition efficiency in wheat spike, for the control of rice blast, was evaluated for three spray nozzles with three volumes of spray. The nozzles used were hollow cone (JA 1-100 L ha-1), jet double plan (DB 110015-150 L ha-1) and jet twin flat (TJ60 11002-200 L ha-1) and the fungicide sprayed was the commercial mixture prothioconazole+trifloxystrobin+ vegetable oil Áureo®. Water sensitive cards were used to capture the spray spectrum were scanned after the passage of the nozzle with the syrup, and, and it also evaluated the severity of symptomatic disease in wheat. The hollow cone nozzle showed a uniformity of the spray distribution with the production of very fine droplets, however it was not as efficient as the plane jets nozzles to control the disease. Nozzles DB 110015 and TJ60 11002, produced fine droplets and were similar to the parameters evaluated.